Filsafat Pengetahuan, Teologia, Mitologi dan Warna Kehidupan Lanjut Usia sebagai Umat Kristianidi HKBP Perumnas II Bekasi Selatan - Mesta Limbong; Manahan. P. Tampubolon; Gutser Siburian (JURNAL ComunitÃ Servizio : Jurnal Terkait Kegiatan Pengabdian kepada Masyarakat, terkhusus bidang Teknologi, Kewirausahaan dan Sosial Kemasyarakatan, 2024)
The elderly is a normal process for every individual. The elderly are also not a burden on themselves or the internal/external environment. For this reason, regulations in Indonesia provide information that the number of elderly people is increasing nationally in Indonesia. The elderly at HKBP Perumnas II South Bekasi are part of the number of elderly in Indonesia. They have programmed activities, but they also need enlightenment from the scientific field and its implications as Christians. The aim of the seminar and discussion with topics related to the Philosophy of Knowledge, Theology, Mythology and the Color of Life for the Elderly as Christians at HKBP Perumnas II South Bekasi" is a form of Community Service with the aim of providing a new perspective for the elderly. The number of participants who attended was 46 participants (73%) and 17 elderly people did not attend (27%). This data provides information that the number of elderly people who attended was still greater than those who were unable to attend. Findings from the community service results: testimonials from elderly people that similar activities had never been done before, elderly participants were very enthusiastic, and hoped that other activities could be carried out, such as health checks.